The Impact of Proton Pump Inhibitors on the Development of Gastric Neoplastic Lesions in Patients With Autoimmune Atrophic Gastritis - Dilaghi, Emanuele; Bellisario, Mario; Esposito, Gianluca; Carabotti, Marilia; Annibale, Bruno; Lahner, Edith (Frontiers in Immunology, 2022)
Introduction: Proton pump inhibitors (PPI) have been widely prescribed as a primary treatment for acid-related disorders. A large body of literature reported several adverse outcomes due to PPI therapy, including an increased risk of gastric cancer(GC). Autoimmune atrophic gastritis(AAG), is a chronic inflammatory disorder affecting the oxyntic mucosa, leading to mucosal atrophy, intestinal metaplasia, reduced gastric acid secretion, up to possible development of dysplasia and intestinal-type GC. Whether PPI use may increase the GC risk in AAG patients has not yet been investigated. We conducted a case-control study in AAG patients to assess the association between the PPI-use before AAG diagnosis and the development of GC at follow-up(FU). Materials and Methods: Patients were included from a prospective cohort of AAG patients (diagnosed 1992-2021) in a referral center for gastric-autoimmunity; all patients adhered to an endoscopic-histological FU program according to MAPS I/II guidelines. At diagnosis, clinical/biochemical data and PPI-use before AAG diagnosis (withdrawn at the time of diagnosis), for at least 12-months, were evaluated. Patients who developed gastric neoplastic lesions(GNL) at FU were considered as cases, patients without diagnosis of GNL at FU were considered as controls. At a total FU of 2.3 years(1-13), 35 cases were identified, controls were matched 2:1 by age(±3 years), gender, and years of FU(n=70), therefore a total of n=105 patients were included in the study. Results: The proportion of PPI users before AAG diagnosis was significantly higher in cases than in controls (54.3% vs 18.6%, p<0.001). At logistic-regression, considering as dependent variable the development of GNL at FU, a positive association was shown for PPI use before AAG diagnosis (OR 9.6, 95%CI 2.3-40.3), while other independent variables as the use of antiplatelets/anticoagulants (OR 2.8, 95%CI 0.7-12.0), age≥50-years (OR 2.0, 95%CI 0.2-18.1), 1st-degree family history for GC (OR 2.4, 95%CI 0.4-15.2), and smoking-habit (OR 0.4, 95%CI 0.1-2.1) were not associated. Conclusions: PPIs use before the diagnosis of AAG appears to considerably increase the risk of subsequent GNL development. Considering the common misuse of PPIs, physicians should regularly reevaluate the appropriateness of ongoing PPIs therapy, in particular in patients with clinical suspicion of or already diagnosed AAG.